Database System Concepts / Second Edition - Korth Henry F; Silberschatz Abraham (Mcgraw Hill Book Company, 1991)
This book shows how to solve many of the problems encountered in designing and using a database system. Preface, Introduction, Entity-Relationship Model, Relational Model, Relational Commercial Languages, Integrity Constraints, Relational Database Design, File and System Structure, Indexing and Hashing, Query Processing, Crash Recovery, Concurrency Control, Transaction Processing, Object-Oriented Model, Extended Relational Systems, Distributed Databases, Security and Integrity, Case Studies, A Network Model, Hierarchical Model, Bibliography, Index.